How can we support the individual breastfeeding experience? Quantitative results from a mixed-methods study - Theresa Philomena Ertlmaier; Oana Costea; Anja Borgmann-Staudt; Monika Berns; Georg Weikert; Mathilde Kersting; Magdalena Balcerek (International Breastfeeding Journal)
Abstract Background Despite the health benefits of breastfeeding only 57% of infants were exclusively breastfed at 4 months postpartum in Germany in 2017–2019. Due to the gap between the actual exclusive breastfeeding (EBF) rates and recommendations, we aimed at investigating further factors influencing breastfeeding duration. Methods This prospective observational study conducted in Berlin, Germany from 11/2022–05/2024 implemented a mixed-methods design with concurrent triangulation. We present quantitative results here. First-time mothers were surveyed at birth and 2, 6 and 12 months postpartum. Breastfeeding status was assessed by asking “How are you currently feeding your child?” and, if anything other than EBF (defined as supply of breastmilk without liquids or solids) was indicated, “I breastfed exclusively until [date]”. Maternal perception was assessed by asking “How comfortable do you currently feel with breastfeeding/feeding your child?”, with comfort referring to well-being/statisfaction/feeling good (German = wohlfühlen). Obstetric and newborn characteristics were collected from recruiting hospital’s health records: an anthroposophic baby-friendly certified hospital (a-BF), a baby-friendly certified hospital (BF) and a university hospital not certified as baby-friendly (non-BF). Data were analysed descriptively and through multivariate analysis. Results Most of the 326 participating mothers had initiated breastfeeding in the delivery room (94.7%). Mothers reported EBF for a median duration of 5.7 months, with 76.6% achieving ≥ 4 months. High levels of maternal comfort with breastfeeding 2 months postpartum were significantly associated with an EBF duration ≥ 4 months (aOR 7.25, CI 95% 2.11, 24.9). An intended EBF duration of 4–7 months (aOR 4.08, CI 95% 0.29, 57.77), higher breastfeeding comfort shortly after birth (aOR 1.79, CI 95% 0.49, 6.59), delivery in the a-BF clinic (aOR 1.59, CI 95% 0.41, 6.14) and high satisfaction regarding breastfeeding support in the hospital (aOR 1.39, CI 95% 0.41, 4.70) increased likeliness of EBF ≥ 4 months. Conclusion Our results emphasize the pivotal role of the mother’s comfort in the breastfeeding process and it’s impact on breastfeeding duration. Strategies to enhace maternal comfort therefore need to be specifically included in maternal care. To explore key aspects of maternal comfort qualitative interviews will address the individual experiences in the breastfeeding journey and identify parent-centred strategies for sustainable breastfeeding.